Tinjauan Yuridis terhadap Penolakan Hak Waris dan Akibat Hukumnya - Eti Mul Erowati; Wiwin Muchtar Wiyono; Teguh Anindito; Aty setyowati; Suprapto Suprapto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to determine the procedure for rejecting inheritance rights and its legal consequences. Normative Juridical Research Method, secondary data sources, this type of research is library research, such as literature in books and scientific works, then analyzed qualitatively using normative juridical analysis methods. From the results of the research and discussion, it can be concluded that: First, the Inheritance Rejection Procedure, in civil law, the rejection of inheritance is carried out with a written statement / deed. After that, the deed of rejection of inheritance is submitted to the court, then the court will check the completeness of the files and the reasons for the rejection. If deemed to meet the requirements, the court will issue a decision regarding the validity or otherwise of the rejection. Second, the Consequences of Renouncing Inheritance, involve changes in the structure of asset distribution. When an heir renounces inheritance, the portion of assets that should have been received by them will be distributed to other heirs. Legal certainty in asset distribution becomes crucial to prevent disputes among heirs. Furthermore, renouncing inheritance can affect the rights and obligations of other heirs. When an heir renounces inheritance, other heirs may have to bear the obligations left by the inherited assets, such as debts. This can impose additional burdens on heirs who receive a larger portion of the inheritance due to such renunciation.